Risk Factors for HIV and AIDS at the Harapan Health Center, East Sentani District, Jayapura Regency in 2023-2024: HIV/AIDS - Almung, Winsi; Hasmi, Hasmi; Pariaribo, Konstantina M.; Bouway, Dolfinus Y.; Tuturop, Katarina L.; Nurdin, Muhammad Akbar (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to determine the risk factors for HIV and AIDS incidence at the Harapan Health Center. Observational analytical research with a case control approach. The sampling technique uses purposive sampling. The population, namely all those who are tested for HIV and AIDS at the 2023-2024 Harapan Health Center, is 965 people with a sample size of 64 additional control cases. The results of bivariate analysis showed a significant relationship between the number of sexual partners (p-v=0.001, OR=21,211, 2,565-175,404) and STI history (p-v=0.000, OR=8,273, 2,622-26,100) with the incidence of HIV and AIDS. Meanwhile, it did not show a significant relationship between age variables (p-v=0.708, OR=1.970, 0.390 - 8.220), gender (p-v=0.439, OR=1.711, 0.616 - 4.769), educational history (p-v=1.000, OR=0.802, 0.218-2.954), marital status (p-v=0.799, OR=1.296, 0.477-3.524), employment status (p-v=0.075, OR=0.345, 0.122-0.974), and the incidence of HIV and AIDS at the Harapan Health Center.